Report on the activities of the 41st Japanese Antarctic Research Expedition (JARE) wintering party, 2000-2001 - Kentaro Watanabe (Antarctic Record, 2009)
The wintering party of the 41st Japanese Antarctic Research Expedition (JARE 41), consisting of 40 members who overwintered at Syowa, carried out most of the planned scientific observations and returned home safely on 28 March 2001. From February 1st 2000, when JARE-41 took over management of Syowa Station from JARE-40, until February 1st 2001, when JARE-41 handed it over to JARE-42, it conducted scientific observations and logistic programs as the fourth year in the 5th five-year plan of JARE. The logistic program consisted mainly of construction work for expansion of a summer party lodging and replacement of facilities. This work was the 9th year of a 10-year plan for maintenance of facilities at Syowa Station. Research activities including snowstorm observations during a stay at Mizuho Station, air-borne collection of air over Syowa, air-borne surveys of the inland atmosphere and collection of 3554 meteorites, including an iron meteorite more than 50 kg in weight, in the Yamato Mountains. Unexpected incidents included collapse of a newly built 10 kW wind generator test plant during a big blizzard in early July, and a leak of diesel oil from a tank in a generator building at Syowa Station in mid-December.